Sifat Fisikokimia Dan Organoleptik Dendeng Daging Kerbau Dengan Persentase Penggunaan Enzim Papain Yang Berbeda - Fitri, Cut aida; ., Dzarnisa; Abubakar, Amhar; Afiq, Fauzan; Salami, Hidayatus (Unpad Press, 2024)
Buffalo meat is tough because buffalo are usually slaughtered when they are old. Apart from that, the high water and protein content in buffalo meat causes the meat to be easily damaged, which can reduce the quality. To prevent or inhibit a decline in quality, preservation is necessary to produce diversified products. This research aims to determine the effect of using the papain enzyme with different percentages on the water content, cooking loss and organoleptic values of buffalo meat jerky. This research was carried out from November 24 to December 24 2023 at the Meat Processing Science and Technology Laboratory, Animal Husbandry Study Program, Faculty of Agriculture, and at the Food and Agricultural Products Analysis Laboratory, Agricultural Products Technology Study Program, Syiah Kuala University, Darussalam, Banda Aceh. This research used a Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications, with the addition of the papain enzyme, namely (0%, 5%, 10% and 15%). The parameters observed were water content, cooking loss, and organoleptics. (taste, aroma, color, texture and tenderness). The final research results showed that the use of the papain enzyme had a significant effect (P<0.05) on the water content of buffalo meat jerky and tended to increase from P0 to P3. The results of statistical analysis using the papain enzyme had no significant effect (P>0.05) on the cooking loss value The Kruskal Wallis test results also showed that the use of the papain enzyme at different percentages had a significant effect (P<0.05) on taste, but the use of the papain enzyme at different percentages had no effect (P>0.05) on color, aroma, texture. , and tenderness.. The use of 10% papain enzyme (P2) produced meat with the best organoleptic value, water content, and cooking loss.